Eigenvalue problem for nonlinear elastic beam equation of fractional order - Khodabakhshi, Neda; Vaezpour, S. Mansour Mansour (Nonlinear Analysis: Modelling and Control, 2017)
In this study, under some suitable assumptions, we determine an explicit eigenvalue interval for the existence of positive solution of singular fractional-order nonlinear elastic beam equation with bending term. Our analysis rely on cone theoretic techniques. Moreover, we consider some special cases and an example to affirm the applicability of the main result.